The POLG Polyglutamine Tract Variants in Iranian Patients with Multiple Sclerosis - KHATAMI, Mehri; HEIDARI, Mohammad Mehdi; MANSOURI, Reza; MOUSAVI, Fatemeh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Khatami M, Heidari MM, Mansouri R, Mousavi F. The POLG Polyglutamine Tract Variants in Iranian Patients with Multiple Sclerosis. Iran J Child Neurol. 2015 Winter; 9(1):37-41. Abstract Objective Multiple Sclerosis (MS) is a common disease of the central nervous system. The interaction between inflammatory and neurodegenerative processes typically results in irregular neurological disturbances followed by progressive disability. Mitochondrial dysfunction has been implicated in neurodegenerative disorders. The DNA polymerase-gamma (POLG) gene, which encodes the catalytic subunit of enzyme responsible for directing mtDNA replication, contains a poly glutamine tract (poly-Q) in the N-terminal, encoded by a CAG sequence in exon 2. Materials & Methods We analyzed the POLG trinucleotide repeats in 40 Iranian patients with MS (27 females and 13 males with an age range of 18–55); and 47 healthy age, gender, and ethnic matched controls were chosen by PCR-SSCP analysis. Results Our results indicated that the most common allele in patients had 10 consecutive CAG repeats (10Q). Other alleles of 11and 12 trinucleotide repeats were detected. We did not find any difference between the CAG repeat length distribution in controls and MS patients. Conclusion No correlation was observed in the POLG gene CAG repeat with pathogenesis of MS, but it looks that other point mutations in POLG gene may have an important role in the disease’s pathogenesis and produced more significant results. References Baranzini SE. Revealing the genetic basis of multiple sclerosis: are we there yet? Curr Opin Genet Dev. 2011 Jun; 21(3):317-24. Hoffjan S, Akkad DA. The genetics of multiple sclerosis: an update 2010. Mol Cell Probes. 2010 Oct; 24(5):237-43. Disanto G, Berlanga AJ, Handel AE, Para AE, Burrell AM, Fries A, et al. Heterogeneity in multiple sclerosis: scratching the surface of a complex disease. Autoimmune Dis. 2010; 2011:932351. International Multiple Sclerosis Genetics C, Wellcome Trust Case Control C, Sawcer S, Hellenthal G, Pirinen M, Spencer CC, et al. Genetic risk and a primary role for cell-mediated immune mechanisms in multiple sclerosis. Nature. 2011 Aug 11; 476(7359):214-9. Mao P, Reddy PH. Is multiple sclerosis a mitochondrial disease? Biochimica et biophysica acta. 2010 Jan; 1802(1):66-79. Inarrea P, Alarcia R, Alava MA, Capablo JL, Casanova A, Iniguez C, et al. Mitochondrial complex enzyme activities and cytochrome C expression changes in multiple sclerosis. Mol Neurobiol. 2014 Feb; 49(1):1-9. Schaller A, Hahn D, Jackson CB, Kern I, Chardot C, Belli DC, et al. Molecular and biochemical characterization of a novel mutation in POLG associated with Alpers syndrome. BMC Neurology. 2011; 11(1):4. Milone M, Brunetti-Pierri N, Tang LY, Kumar N, Mezei MM, Josephs K, et al. Sensory ataxic neuropathy with ophthalmoparesis caused by POLG mutations. Neuromuscul Disord. 2008 Aug; 18(8):626-32. Azrak S, Ayyasamy V, Zirpoli G, Ambrosone C, Bandera EV, Bovbjerg DH, et al. CAG repeat variants in the POLG1 gene encoding mtDNA polymerase-gamma and risk of breast cancer in African-American women. PLoS One. 2012; 7(1):e29548. Eerola J, Luoma PT, Peuralinna T, Scholz S, Paisan-Ruiz C, Suomalainen A, et al. POLG1 polyglutamine tract variants associated with Parkinson’s disease. Neurosci Lett. 2010 Jun 14; 477(1):1-5. Rovio A, Abel J, Ahola A, Andres A, Bertranpetit J, Blancher A, et al. A prevalent POLG CAG microsatellite length allele in humans and African great apes. Mammalian genome. 2004; 15(6):492-502. Spelbrink JN, Toivonen JM, Hakkaart GA, Kurkela JM, Cooper HM, Lehtinen SK, et al. In vivo functional analysis of the human mitochondrial DNA polymerase POLG expressed in cultured human cells. Journal of Biological Chemistry. 2000; 275(32):24818-28. Williams AJ, Paulson HL. Polyglutamine neurodegeneration: protein misfolding revisited. Trends in neurosciences. 2008; 31(10):521-8. Luoma P, Eerola J, Ahola S, Hakonen A, Hellström O, Kivistö K, et al. Mitochondrial DNA polymerase gamma variants in idiopathic sporadic Parkinson disease. Neurology. 2007; 69(11):1152-9. Heidari MM, Houshmand M, Hosseinkhani S, Nafissi S, Scheiber-Mojdehkar B, Khatami M. Association between trinucleotide CAG repeats of the DNA polymerase gene (POLG) with age of onset of Iranian Friedreich’s ataxia patients. Neurol Sci. 2008 Dec; 29(6):489-93. Heidari MM, Khatami M, Talebi AR. The POLG Gene Polymorphism in Iranian Varicocele-Associated Infertility Patients. Iran J Basic Med Sci. 2012 Mar; 15(2):739-44. Jensen M, Leffers H, Petersen JH, Nyboe Andersen A, Jorgensen N, Carlsen E, et al. Frequent polymorphism of the mitochondrial DNA polymerase gamma gene (POLG) in patients with normal spermiograms and unexplained subfertility. Hum Reprod. 2004 Jan; 19(1):65-70. Taanman JW, Schapira AH. Analysis of the trinucleotide CAG repeat from the DNA polymerase gamma gene (POLG) in patients with Parkinson’s disease. Neurosci Lett. 2005 Mar 7; 376(1):56-9. Wong LJ, Naviaux RK, Brunetti-Pierri N, Zhang Q, Schmitt ES, Truong C, et al. Molecular and clinical genetics of mitochondrial diseases due to POLG mutations. Hum Mutat. 2008 Sep; 29(9):E150-72. Kumleh HH, Riazi GH, Houshmand M, Sanati MH, Gharagozli K, Shafa M. Complex I deficiency in Persian multiple sclerosis patients. Journal of the Neurological Sciences. 2006 4/15/; 243(1–2):65-9. Ebers GC, Sadovnick AD, Dyment DA, Yee IML, Willer CJ, Risch N. Parent-of-origin effect in multiple sclerosis: observations in half-siblings. The Lancet. 2004; 363(9423):1773-4. Harding A, Sweeney M, Miller D, Mumford C, Kellar-Wood H, Menard D, et al. Occurrence of a multiple sclerosis-like illness in women who have a Leber’s hereditary optic neuropathy mitochondrial DNA mutation. Brain: a journal of neurology.1992; 115(4):979-89. Ahari SE, Houshmand M, Panahi MS, Kasraie S, Moin M, Bahar MA. Investigation on mitochondrial tRNA (Leu/Lys), NDI and ATPase 6/8 in Iranian multiple sclerosis patients. Cell Mol Neurobiol. 2007 Sep; 27(6):695-700. Mahad DJ, Ziabreva I, Campbell G, Lax N, White K, Hanson PS, et al. Mitochondrial changes within axons in multiple sclerosis. Brain: a journal of neurology. 2009 May; 132(Pt 5):1161-74.